2020
DOI: 10.1093/cercor/bhaa307
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Temporal Presentness in the Precuneus: A Cross-linguistic fMRI Study based on Speech Stimuli

Abstract: The position of any event in time could be in the present, past, or future. This temporal discrimination is vitally important in our daily conversations, but it remains elusive how the human brain distinguishes among the past, present, and future. To address this issue, we searched for neural correlates of presentness, pastness, and futurity, each of which is automatically evoked when we hear sentences such as “it is raining now,” “it rained yesterday,” or “it will rain tomorrow.” Here, we show that sentences … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The fact that the strongest response of the precuneus is to presentness is presumably important for survival, with a clear evolutionary advantage in focussing upon an accurate representation of the current situation of the individual and state of affairs of the external world. Further, the response to the 'future' comes second, as is again reasonable given the need to make plans for upcoming events, while response to the 'past' comes third, perhaps since 'it is no use crying over spilt milk' ( [85] figure 3D and discussion).…”
Section: The Universal Bootstrap 41 Chronogenesis: the Interrelation ...mentioning
confidence: 99%
See 3 more Smart Citations
“…The fact that the strongest response of the precuneus is to presentness is presumably important for survival, with a clear evolutionary advantage in focussing upon an accurate representation of the current situation of the individual and state of affairs of the external world. Further, the response to the 'future' comes second, as is again reasonable given the need to make plans for upcoming events, while response to the 'past' comes third, perhaps since 'it is no use crying over spilt milk' ( [85] figure 3D and discussion).…”
Section: The Universal Bootstrap 41 Chronogenesis: the Interrelation ...mentioning
confidence: 99%
“…In particular it has been demonstrated that the precuneus plays a central role in the neural basis for our subjective experience of the present, that is the 'now' of our time perception [85]. In fact precuneus activation is found to be significant in association with subjective feelings of the past, present and future, as evoked by speech stimuli, with the response up to three times greater for the experience of 'presentness', in a manner that is independent of the language used.…”
Section: The Universal Bootstrap 41 Chronogenesis: the Interrelation ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, time perception is impaired in disorders of the precuneus/posterior cingulate gyrus 35 and supramarginal gyrus 36 . In particular, the precuneus may contribute to our sense of “presentness”, providing the “now” in the passage of time 37 , 38 .…”
mentioning
confidence: 99%